ASSOCIATION BETWEEN FIRST TRIMESTER OBESITY AND SOME MATERNAL CHARACTERISTICS - Kristina Skeparovska; Jankulovski, Nikola; Pranvera Izairi; Svetozar Antovik (Македонско лекарско друштво = Macedonian Medical Association, 2020)
Abstract Introduction. Obesity in pregnant women has substantial negative impact on both pregnancy and labor/delivery. The aim of this article was to determine first trimester obesity-frequency, and its association with some maternal history data. Methods. In this cross-sectional study, 809 first trimester pregnant women were evaluated for obesity defined as BMI ≥30. The data were collected via a questionnaire. Results. BMI ≥30 had17.3% of all participants, 17.0% of them were Macedonian and 17.5% Albanian. BMI ≥30 had 23.9%of those with completed primary school, 16.4% of those with completed high school, and 14.8% of those with university degree; 18.7% of those with total family income less than 350 euros, 14.9% of those with total family income between 350-700 euros, and 14.8% of those with total family income above 700 euros. BMI ≥30 had 13.2% of nulliparous, and 20.6% of parous women. Among smokers, BMI ≥30 had 28.8%, but only 15.3% in nonsmokers. Regarding the IPI (interpregnancy interval), 26.2% in those with IPI ≤12 months had BMI ≥30, and 19.6% of those with IP I>12 months. Women aged40 years and over had BMI ≥30 in 40% of casesversus 16.8% of pregnant women younger than 40 years. Conclusion. Obesity showed statistically significant negative association with level of education (p=0.010), positive correlation with smoking (p=0.003), age of the mother (p=0.019) and parity (p=0.006); obesity showed negative, but statistically insignificant association with IPI and family wealth, and showed no association with nationality.
АСОЦИЈАЦИЈА НА ПРИСУТЕН ОБЕЗИТЕТ ВО ПРВ ТРИМЕСТАР ОД БРЕМЕНОСТА СО ОДРЕДЕНИ МАЈЧИНИ ОБЕЛЕЖЈА
Keywords: obesity; pregnancy; smoking; parity; age